2017
DOI: 10.21608/ejh.2017.3697
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Study on the Effect of Constant Light Exposure on T Lymphocyte Subsets in the Thymus and Lymph Node of Male Albino Rats

Abstract: Background: Today there is a widespread exposure to high levels of light at night. . This causes divergence from the natural environment and leads to significant implications on the circadian rhythm. Constant light exposure inhibits melatonin secretion and increases serum concentration of corticosterone. The immune system is very sensitive to stress. Aim of the Work: to study the effect of chronic exposure to constant light (as a model of stress) on the T lymphocytes populations and distribution in the thymus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Similar finding was reported by Escribano et al [11] who attributed this to increased lipoperoxide levels and reduced anti-oxidative stress biomarkers. In agreement, Rifaai and Abd El Baky [35] demonstrated that 1-month period of constant light caused structural changes in the rat thymus. These changes might cause autoimmune response.…”
Section: Discussionsupporting
confidence: 60%
“…Similar finding was reported by Escribano et al [11] who attributed this to increased lipoperoxide levels and reduced anti-oxidative stress biomarkers. In agreement, Rifaai and Abd El Baky [35] demonstrated that 1-month period of constant light caused structural changes in the rat thymus. These changes might cause autoimmune response.…”
Section: Discussionsupporting
confidence: 60%